A comprehensive review on indigenous therapeutic approaches in kidney care using Ayush medicine - Niharika; Parveen, Rabea; Parveen, Bushra; Umar, Shahid; Ahmad, Sayeed (Frontiers in Pharmacology, 2026)
Chronic kidney disease (CKD) presents a significant global health concern due to its progressive impact on kidney function, and associated complications. This narrative review highlights the role of traditional system of medicine and comprehensive approach to managing chronic kidney disease (CKD) including their molecular mechanisms and therapeutic roles. The interdependence of physical, mental, and spiritual wellbeing is acknowledged by AYUSH, and other indigenous traditions, which emphasize on botanical drugs with proven nephroprotective qualities in addition to dietary changes, lifestyle adjustments, and mind-body therapies. For instance, traditional botanical drugs have shown nephroprotective effects in both preclinical and clinical trials. Yoga activities promote overall wellbeing, which is particularly beneficial for individuals with chronic kidney disease. Our aim is to explore and integrate traditional medicine with modern nephrology practices for enhancing CKD management. However, the review presents the brief importance of this integration and challenges such as the need for robust clinical trials to substantiate safety and efficacy. It also discusses the legal and quality control concerns related to botanical drugs. Overcoming these hurdles is paramount for the successful assimilation of traditional medicine systems with modern healthcare practices. The review also contains the synergistic blend of contemporary nephrology with ancient healing systems like AYUSH offering a compelling approach to CKD treatment and nephroprotection.